A RETROSPECTIVE OBSERVATIONAL STUDY ON THE EFFECTS OF TYPE 2 DIABETES AND ITS MANAGEMENT ON INDIVIDUALS WITH SEVERE COVID-19 PATIENTS’ PROGNOSIS. - Guha, Shaibal; Das, Amit Kumar (Student’s Journal of Health Research Africa, 2023)
Background: Type 2 diabetes (T2D) as a worldwide chronic disease combined with the COVID-19 pandemic necessitates improving the management of hospitalized COVID-19 patients with preexisting T2D to reduce complications and the risk of death. Methods: In this retrospective study, the clinical characteristics of 193 patients with severe covid-19 were gathered. 48 patients with severe covid-19 had diabetes, while 145 patients (the control group) did not. Results: 48 (24.9%) of 193 patients with severe covid-19 had diabetes. In comparison to patients with severe covid-19 who did not have diabetes, those with diabetes were elderly, more likely to require mechanical ventilation and ICU admission, and had a higher mortality rate. Moreover, patients with severe covid-19 and diabetes had elevated levels of leukocyte count, neutrophil count, high-sensitivity C reaction protein, procalcitonin, ferritin, interleukin (IL) 2 receptor, IL-6, IL-8, tumour necrosis factor, D-dimer, fibrinogen, lactic dehydrogenase, and N-terminal pro-brain natriuretic peptide. Among patients with severe covid-19 and diabetes, men were more likely to not survive [30 (76.9%) vs. 9 (23.1%)]. Conclusion: The mortality rate among patients with severe covid-19 and diabetes is substantial. Diabetes may increase the likelihood of mortality.